Ages and kinematics of chemically selected, accreted Milky Way halo stars. Issue 4 (3rd February 2020) - Das, Payel; Hawkins, Keith; Jofré, Paula
ABSTRACT: We exploit the [Mg/Mn]-[Al/Fe] chemical abundance plane to help identify nearby halo stars in the 14 th data release from the APOGEE survey that have been accreted on to the Milky Way. Applying a Gaussian Mixture Model, we find a 'blob' of 856 likely accreted stars, with a low disc contamination rate of ∼7 per cent. Cross-matching the sample with the second data release from Gaia gives us access to parallaxes and apparent magnitudes, which place constraints on distances and intrinsic luminosities. Using a Bayesian isochrone pipeline, this enables us to estimate new ages for the accreted stars, with typical uncertainties of ∼20 per cent. This does not account for systematic uncertainties. Our new catalogue is further supplemented with estimates of orbital parameters. The blob stars span [Fe/H] between −2.5 to −0.5, and [Mg/Fe] between −0.1 to 0.5. They constitute ∼30 per cent of the metal-poor ([Fe/H] < −0.8) halo at [Fe/H] ∼ −1.4. Our new ages mainly range between 8 to 13 Gyr, with the oldest stars the metal-poorest, and with the highest [Mg/Fe] abundance. If the blob stars are assumed to belong to a single progenitor, the ages imply that star formation lasted 5 Gyr after which the system merged with our Milky Way around 8 Gyr ago. Dynamical arguments suggest that such a single progenitor would have had a total mass of 10^11 M_, similar to that found by other authors using chemical evolution models and simulations.